Uncertainty in Banorte’s overdue credit card portfolio and its effect on the minimum wage - Ríos González, Daniel Ríos González (Revista Internacional de Salarios Dignos, 2022)
One of the most affected sectors during the pandemic was banking, specifically, the levels of overdue credit card portfolios. The objective of this study is to calculate the probability of overdue levels on a credit card portfolio. In addition, based on CNBV’s information, a gamma distribution is fitted to estimate the overdue percentages. The results show that with a probability of 11%, the overdue portfolio percentage might return to its average levels before the pandemic, that is, 6.3% which is equivalent to 2,593 million Mexican pesos. Although the likelihood is small, as the acquisition of credits grows and the number of restructured credits decreases, this probability will increase. This analysis is a starting point for forecasting the overdue portfolio percentage; however, we do not consider some factors such as the regulatory framework, internal policies in credit models, and growth strategies in the banking sector. All these factors could lead to a more precise probability as the credit card portfolio begins to mature in times of non-pandemic. On the other hand, involving minimum wages could be an adequate strategy to predict or control the overdue portfolio; though its coefficient of determination is not close to 1, the analysis developed shows that the higher the minimum wage is, the overdue portfolio decreases.